Estudio de factibilidad para la creación de una empresa de faenamiento y comercialización de especies avícolas en el cantón Buena Fé año 2014 - Jiménez Brito, Ana María (2015)
Poultry has different stages and processes, which involved large and small. Currently in Buena Fé Canton province of Los Ríos there are few companies slaughtering chickens, so the opportunity arose in the medium term to establish a poultry slaughtering plant, which is the process of transforming the live chicken in a ready for cooking, they will be offered to the client, requiring the submission such as: whole chickens with visors, whole chicken without visors. The main goal is to capture a share of the wholesale customers and consumers chickens at Buena Fé Canton, hoping that the product meets the needs at minimum cost. In developing the project, the feasibility of implementing a slaughtering poultry plant in Canton Buena Fé province of Los Rios was analyzed , taking into account the following: Market research : Using survey based on a sample of a segment were determined in the canton Buena Fé , their determining outcomes in the buying decision of potential customers , their needs, what are their main competitors and the threat , how the product is marketed is based were analyzed , which will be the most appropriate position so we could market strategies , plus SWOT analysis , slaughter processes, equipment used in the slaughter of chickens was performed , from entering the chicken feet until it is totally dressing and packed for sale; to apply the best practices of slaughter and get fit for human consumption in the business studio product , investment in fixed assets was estimated by the given information in a technical report , costs for slaughtering chickens given daily volume, administrative and sales according to organizational study and resources distribution expenses. Revenues were estimated based on the market study where we obtained the reference potential sales and price per pound of chicken projecting reference to five years taking market movement in previous years. Finally all the collected data a cash flow where we got the results of IRR and NPV , Payback ( time inversion recovery ) was performed , and we proceeded to determine the feasibility of the project.